Mathematical modeling of the influence of the force closure of machine retaining device on the errors of the planes shape - Пипкин, Юрий Владимирович; Зелинский, Анатолий Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The results of parametric research on the mathematical model in MATLAB Simulink influence the characteristics of the force closure of machine retaining devices on the errors formation of the planes shape surfaces obtained by cutting blade are presented